Powerful Reports and Proposals - Forsyth P. Patrick (The Sunday Times)
Provides practical pointers for those who need to impress, convince and persuade their colleagues or clients. Using checklists and examples, this second edition explains how to make a plan of what to write, transfer ideas onto paper and edit them. It is useful for business persons, and helps anyone write appropriately for their target readers.